ДИСКУСІЙНЕ ПИТАННЯ ЩОДО ДАТИ ЗАСНУВАННЯ СТАРОБЕРДЯНСЬКОГО ЛІСНИЦТВА (Zaporizhzhia Historical Review, 2021)
The foundation of the Ministry of state property in 1838 started a new period in the development of the massive steppe foresting. In 40-es due to the order of the government, the Velykoanadols’k and Staroberdynsk forestries were founded. The date of the foundation of the Staroberdynsk forestry and its school of forsters has been a disputable point among the scholars for many years. The next point worthy of consideration is the reason of the term of foundation of the Staroberdyansk forestry that tookplace some years later after the Velykoanadolsk one.